Macro/Microtesting and Damage and Degradation of Sandstones under Dry-Wet Cycles - Xinrong Liu; Zijuan Wang; Yan Fu; Wen Yuan; Luli Miao (Advances in Materials Science and Engineering)
In terms of the degradation of mechanical parameters of rock mass in the hydrofluctuation belt of a reservoir bank slope arising from rainfall and the reservoir level fluctuation, the moderately weathered sandstone in a side slope of the Three Gorges Reservoir Region is selected as a research object to carry out “drying-saturation-drying” tests for disks with two thicknesses (h=25 mm, h=50 mm) in different cycles; a spiral CT machine, an ultrasonic velocity meter, and a light Schmidt hammer are utilzed to conduct nondestructive testing on dry-wet cycles; through the Brazilian splitting test, the uniaxial tensile strength of “dry” and “saturated” sandstones under different dry-wet cycles is obtained. The research shows that, with the increase of the dry-wet circles (n), the longitudinal wave velocity and the rebound strength of sandstones are linearly decreased with n; the uniaxial tensile strength of sandstones and the mean CT number of cross sections are logarithmically decreased with n; the fitting equation of macro/micromechanical parameters and dry-wet cycles (n) of sandstones is raised, which is provided as a reference basis for the weathering process of sandstones under dry-wet cycles.